2020
DOI: 10.1186/s12913-020-05715-3
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of deprived patients on diabetes self-management programmes delivered by the local primary care team: a qualitative study on facilitators and barriers for participation, in France

Abstract: Background Diabetes self-management education (DSME) is an effective intervention for patients with type 2 diabetes mellitus (T2DM); nevertheless, patient participation in this type of programme is low. Implementation of DSME programmes in primary care practices by the local multi-professional team is a potential strategy to improve access to DSME for T2DM patients. The aim of this study was to identify perceived facilitators and barriers by patients to participation in local DSME delivered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Individual, social and familial factors are other obstacles on the way to participating in the self-care training schemes. In line with the current study, previous studies have suggested hectic work and business and difficulty in getting time off work as social obstacles to the training and self-care of diabetic patients [ 23 , 24 ]. Previous studies showed that patients who are unemployed or retired are more likely to attend in self-management programs than those who work full or part-time [ 10 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Individual, social and familial factors are other obstacles on the way to participating in the self-care training schemes. In line with the current study, previous studies have suggested hectic work and business and difficulty in getting time off work as social obstacles to the training and self-care of diabetic patients [ 23 , 24 ]. Previous studies showed that patients who are unemployed or retired are more likely to attend in self-management programs than those who work full or part-time [ 10 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although training is one of the most effective ways to enhance self-care conduct, weakness in contents and unsuitable teaching techniques can hinder the use of the educational programs, which are also mentioned by the patients in the present study. In another study, unsuitable teaching content is said to be one reason for the disinterest in such schemes [ 24 ]. Using supplementary books and reflecting the experience of cured patients by themselves were suggested by the interviewees.…”
Section: Discussionmentioning
confidence: 99%
“…The key finding in this study was the importance of relationships, and how this underpinned engagement, echoing Mc Kenzie et al findings ( 37 ) and those of Allory et al ( 43 ). In the latter study, people with T2D living in a deprived area of France who attended a diabetes self-management education programme spoke of community relationships—the familiarity of environment (being in place) and with educators (being in relation)—as important facilitators in engagement ( 43 ). In our study, relationships were multi-directional between HCPs, between attendees, between HCPs and attendees, and between all and the external community, encapsulating the meaning of “whānau”.…”
Section: Discussionsupporting
confidence: 80%
“…This knowledge empowerment could be likened to social capital—a “knowledge capital”—that can only enhance “societies”-management of T2D, beyond that of “self”-management. Allory et al ( 43 ) stress that a key objective of T2D education programmes should be to develop new social links for attendees as social difficulties and concerns can create limited social access and promote isolation for marginalised populations. We suggest that growing both social and knowledge capital should be key aims of lifestyle programmes such as DCEP and primary care providers should be supported centrally (by government health policies and funding) to support such initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the program, interviews were conducted to identify perceived barriers to PCC delivery for patients with multimorbidity in the primary care setting. This approach is similar to that used in previous qualitative studies of barriers to primary care delivery [ 46 , 47 ]. Sampling was purposive, with the intent of interviewing at least one GP and one NP per practice.…”
Section: Methodsmentioning
confidence: 99%